(untitled) (Pakistan Journal of Science, 2022)
The research aims to investigate the tehsils population growth and land use change. The study was conducted in megacity Lahore which is the second largest city of Pakistan. The urbanization is a process which enables towns and cities to grow by human migration from rural to urban areas. In addition, it is a progressive population increase in cities and towns, which is hugely influenced by the notion achieved by towns and cities. Changing the Earth is a very regional trend with effects on the environment scale on the regional scale that may vary in the sign of the change. In order to study LULC changes in a city like Lahore, four Landsat satellite images of Lahore district were acquired for 1990, 2000, 2010 and 2020 with the resolution of 30 meters. By using Arc GIS the satellite images were digitized to know the land use change in Lahore from 1990-2020. Lahore tehsils population detection maps from 1990-2020 using GIS were used to show the tehsils population. According to the present study of tehsils population of Lahore including cantonment, city, Model town, raiwind and Shalimar, as observed, the highest trend of population is towards raiwind tehsil. The second highest populating growth is in tehsil model town and the lowest trend of populating is in tehsil Shalimar. Temporal analysis of population and land use change data for the last thirty years from 1990-2020 demonstrates that Lahore’s population has increased 156%. Built-up area has increased 57%, vegetation and green cover decreased by 21%, the open area has decreased by 42% and water bodies decreased by 58%..